2021
DOI: 10.1002/1873-3468.14172
|View full text |Cite
|
Sign up to set email alerts
|

Distinct classes of misfolded proteins differentially affect the growth of yeast compromised for proteasome function

Abstract: Maintenance of the proteome (proteostasis) is essential for cellular homeostasis and prevents cytotoxic stress responses that arise from protein misfolding. However, little is known about how different types of misfolded proteins impact homeostasis, especially when protein degradation pathways are compromised. We examined the effects of misfolded protein expression on yeast growth by characterizing a suite of substrates possessing the same aggregation‐prone domain but engaging different quality control pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 81 publications
(116 reference statements)
1
3
0
Order By: Relevance
“…As with dfm1Δ cells, this effect was specific to membrane protein expression, as expression of CPY* in rpn4Δ cells did not result in a growth defect ( S4B Fig ). This is in line with previous research demonstrating Rpn4 is activated in response to misfolded membrane protein accumulation and that misfolded membrane protein expression can result in proteasome impairment, even in WT cells [ 54 , 55 ]. Finally, we tested a transcription factor that can regulate Rpn4 and has many overlapping transcriptional targets with Rpn4, Pdr1 [ 56 ], and did not observe any growth defect in pdr1Δ +Hmg2 cells ( S4C Fig ).…”
Section: Resultssupporting
confidence: 92%
“…As with dfm1Δ cells, this effect was specific to membrane protein expression, as expression of CPY* in rpn4Δ cells did not result in a growth defect ( S4B Fig ). This is in line with previous research demonstrating Rpn4 is activated in response to misfolded membrane protein accumulation and that misfolded membrane protein expression can result in proteasome impairment, even in WT cells [ 54 , 55 ]. Finally, we tested a transcription factor that can regulate Rpn4 and has many overlapping transcriptional targets with Rpn4, Pdr1 [ 56 ], and did not observe any growth defect in pdr1Δ +Hmg2 cells ( S4C Fig ).…”
Section: Resultssupporting
confidence: 92%
“…Furthermore, a recent study has shown that expression of a cytoplasmic model misfolded protein NBD2* in the rpn4 mutant did not lead to slower cell growth, while the expression of several membrane misfolded mutant proteins resulted in slower growth of the rpn4 mutant. 65 Based on that finding, it is possible that protein quality control mutants other than rpn4 may have a synthetic phenotype with human tau.…”
Section: Discussionmentioning
confidence: 99%
“…membrane misfolded mutant proteins resulted in slower growth of the rpn4 mutant. 65 Based on that finding, it is possible that protein quality control mutants other than rpn4 may have a synthetic phenotype with human tau.…”
Section: Discussionmentioning
confidence: 99%
“…Maintenance of the proteome is important in the stress response system [4]. This dynamic equilibrium is mediated by the coupling of ubiquitin with intracellular proteins for their selective degradation in eukaryotes.…”
Section: Introductionmentioning
confidence: 99%